NAD-biosynthetic enzyme NMNAT1 reduces early behavioral impairment in the htau mouse model of tauopathy - Rossi, Francesca; Geiszler, Philippine C.; Meng, Weina; Barron, Matthew; Prior, Malcolm; Herd-Smith, Anna; Loreto, Andrea; Yanez Lopez, Maria; Faas, Henryk; Pardon, Marie-Christine; Conforti, Laura (Elsevier, 2018)
NAD metabolism and the NAD biosynthetic enzymes nicotinamide nucleotide adenylyltransferases (NMNATs) are thought to play a key neuroprotective role in tauopathies, including Alzheimer’s disease. Here, we investigated whether modulating the expression of the NMNAT nuclear isoform NMNAT1, which is important for neuronal maintenance, influences the development of behavioral and neuropathological abnormalities in htau mice, which express non-mutant human tau isoforms and represent a model of tauopathy relevant to Alzheimer’s disease. Prior to the development of cognitive symptoms, htau mice exhibit tau hyperphosphorylation associated with a selective deficit in food burrowing, a behavior reminiscent to activities of daily living which are impaired early in Alzheimer’s disease. We crossed htau mice with Nmnat1 transgenic and knockout mice and tested the resulting offspring until the age of 6 months. We show that overexpression of NMNAT1 ameliorates the early deficit in food burrowing characteristic of htau mice. At 6 months of age, htau mice did not show neurodegenerative changes in both the cortex and hippocampus, and these were not induced by downregulating NMNAT1 levels. Modulating NMNAT1 levels produced a corresponding effect on NMNAT enzymatic activity but did not alter NAD levels in htau mice. Although changes in local NAD levels and subsequent modulation of NAD-dependent enzymes cannot be ruled out, this suggests that the effects seen on behavior may be due to changes in tau phosphorylation. Our results suggest that increasing NMNAT1 levels can slow the progression of symptoms and neuropathological features of tauopathy, but the underlying mechanisms remain to be established.